A Survey on Diabetic Subjects to Study the Prevalence and Pattern of Dyslipidaemia - Bhardwaj Priyanka; Chaudhary Vijay; Chaudhary Minakshi (AYUSHDHARA, 2023)
Diabetes has become a major concern for medical feternity being one of the most common disorders and associated with a high mortality and morbidity because of the complications associated, dyslipidemia being one of them. Need of the hour is to study the prevalence, patterns and risk factors associated with the condition of dyslipidemia in diabetes. Materials and methods: A survey study was carried out on 220 subjects visiting the O.P/I.P, Department of Kayachikitsa, Rajiv Gandhi Government Post Graduate Ayurvedic Hospital, Paprola (HP) on a pre-designed questionnaire. Observations and results: Prevalence of dyslipidemia was found to be 92.72% which was on higher side in females (96.92%) as compared to males (86.67%). Mixed diet and lack of physical exercise were also found to be one of the major risk factors. Anthropometric parameters studied in the survey were on higher side as compared to suggested cut off values. Glycemic status of the patients was found to be significantly correlated with S. Cholesterol, S.Triglycerides and VLDL. Conclusions: Present study revealed high prevalence of Dyslipidemia among Diabetic subjects. Thus, awareness should be made in healthcare providers as well as in patients of Diabetes regarding changing the lifestyle, dietary modifications and regular follow ups to offer a better management of the disease.